2018
DOI: 10.1103/physreva.97.012123
|View full text |Cite
|
Sign up to set email alerts
|

Nonanomalous measure of realism-based nonlocality

Abstract: Based on a recently proposed model of physical reality and an underlying criterion of nonlocality for contexts [A. L. O. Bilobran and R. M. Angelo, Europhys. Lett. 112, 40005 (2015)], we introduce a quantifier of realismbased nonlocality for bipartite quantum states, a concept that is profoundly different from Bell nonlocality. We prove that this measure reduces to entanglement for pure states, thus being free of anomalies in arbitrary dimensions, and identify the class of states with null realism-based nonloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…In Ref. [45], the measure N (ρ) = max A,B N AB (ρ) was introduced as a genuine non-anomalous quantifier of realism-based non-locality and shown to be fundamentally different from Bell non-locality. In addition, it has been shown that N (ρ) is rather resilient to local disturbances, occupies a peculiar position within a given hierarchy of non-classicality quantifiers [46], is the only nonclassical aspect that survives in the asymptotic dynamics of two non-interacting quantum walkers [47], and admits a formulation for tripartite states [48].…”
Section: Elements Of Realitymentioning
confidence: 99%
“…In Ref. [45], the measure N (ρ) = max A,B N AB (ρ) was introduced as a genuine non-anomalous quantifier of realism-based non-locality and shown to be fundamentally different from Bell non-locality. In addition, it has been shown that N (ρ) is rather resilient to local disturbances, occupies a peculiar position within a given hierarchy of non-classicality quantifiers [46], is the only nonclassical aspect that survives in the asymptotic dynamics of two non-interacting quantum walkers [47], and admits a formulation for tripartite states [48].…”
Section: Elements Of Realitymentioning
confidence: 99%
“…By maximizing the contextual realism-based nonlocality over all possible contexts, Gomes and Angelo then introduced the bipartite realism-based nonlocality [28]…”
Section: Preliminary Conceptsmentioning
confidence: 99%
“…Inspired by the lack of such a clear link between realism and violations of the local causality hypothesis, a notion of nonlocality has recently been put forward that makes explicit use of a criterion of realism [27]. This novel aspect of nonlocality counts with a nonanomalous quantifier, is remarkably more resilient to noise than other quantum resources, and reduces to bipartite entanglement for pure states [28,29].…”
mentioning
confidence: 99%
“…where The BA criterion for the occurrence of realism, (2), and the quantification of its violation, (3), count by now with further developments and applications [46][47][48][49]. All these works are, however, strictly connected with discrete-spectrum observables.…”
Section: Basic Concepts and Uncertainty Relationmentioning
confidence: 99%
“…A few years ago, Bilobran and Angelo (BA) introduced a measurementbased criterion of reality which allowed for the quantification of the degree of reality of a discrete-spectrum observable for a given multipartite quantum state [45]. This approach led to further foundational developments, as, for instance, the definition of the realism-based nonlocality [46,47], which captures nonlocal aspects that are dramatically different from Bell nonlocality, and the derivation of an information-reality complementarity relation [48], which is shown to apply even to scenarios of weak disturbances. Interestingly, this framework received experimental corroboration via weak measurements implemented in a photonic platform [49].…”
Section: Introductionmentioning
confidence: 99%